Unpacking University students’ perceptions of teamwork in community engagement project - Shaidin, Sumayyah; Jamil Azhar, Sheik Badrul Hisham; Norddin, Atikah (Universiti Teknologi MARA, Kedah, 2024)
In the context of community engagement projects, understanding students’ perceptions of teamwork is crucial for enhancing collaborative learning experiences. This qualitative study investigates how university students describe their learning encounters with teamwork during the planning and execution of a community engagement project. This research aims to unravel the nuances of teamwork experiences within real-world community contexts. Samples of their selfreflection on their teamwork-related experience were collected from 5 final-semester undergraduates of a local university to capture their narratives about teamwork. These students were tasked to conduct a community engagement project as a team as part of their subject fulfilment at a local government secondary school. Thematic analysis was employed to identify recurring themes related to teamwork perceptions. Results show some insights into positive aspects of teamwork, challenges dealing with other teammates and learning aspects they have achieved. This research sheds light on the intricate interplay between students’ perceptions of teamwork and community engagement experiences. By unpacking these perceptions, educators and practitioners can create more meaningful and impactful community-based learning opportunities. Studying students’ teamwork experiences enriches community engagement practices, promotes strategic partnerships between universities and local organisations, and empowers both students and the communities they serve. In due course, this study contributes to the broader goal of nurturing socially responsible and collaborative citizens.